2018
DOI: 10.1017/sjp.2018.8
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Coping between Competitive Anxiety and Sport Commitment in Adolescent Athletes

Abstract: Framed in cognitive-motivational-relational theory of emotions (Lazarus, 1999), this study aimed to test how coping mediated the relationship between competitive anxiety and sport commitment in a sample of adolescent athletes. Five-hundred adolescents (M = 16.42; SD = 1.54) participated in our study. Participants completed competitive anxiety, coping, and sport commitment measures. We defined the measurement model using confirmatory factor analysis and exploratory structural equation modeling; and compared two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0
24

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 35 publications
3
9
0
24
Order By: Relevance
“…In addition, sportsmen and women with a high level of sporting commitment increase team performance (Gross et al, 2018), collective identity (Wann and Pierce, 2003), or the perception of task-and careoriented climates among team members (Torregrosa et al, 2011;Hall et al, 2017). On the contrary, and in the same way as the results of the present work, engagement already in young athletes decreases the anxious perception of competitive situations (Pons et al, 2018) and enhances positive emotions (McCarthy, 2011;Friesen et al, 2013) in young athletes.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In addition, sportsmen and women with a high level of sporting commitment increase team performance (Gross et al, 2018), collective identity (Wann and Pierce, 2003), or the perception of task-and careoriented climates among team members (Torregrosa et al, 2011;Hall et al, 2017). On the contrary, and in the same way as the results of the present work, engagement already in young athletes decreases the anxious perception of competitive situations (Pons et al, 2018) and enhances positive emotions (McCarthy, 2011;Friesen et al, 2013) in young athletes.…”
Section: Discussionsupporting
confidence: 66%
“…With regard to its links with burnout, sport commitment has maintained negative relationships with both emotional exhaustion, sports devaluation, and reduced personal fulfillment throughout most of the scientific literature (Gustafsson et al, 2017b;Bicalho and Da Costa, 2018) both in individual (Weiss et al, 2001) and team sports (Cresswell and Eklund, 2006;Curran et al, 2013) and in professional sports (Hill et al, 2008) or in lower categories (Harris and Watson, 2011;Pons et al, 2018). However, in team sports, it has been argued in recent studies that being committed to the team is linked to an increased deterioration in sporting self-fulfillment, essentially when the pride and honor associated with belonging to a team is present, often combined with a sense of responsibility and a desire to maintain standards of performance in order to contribute and be useful to the team (Woods et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Fonte: os autores Em relação as análises por sexo, observou-se na presente revisão que os resultados de três estudos não demonstraram diferenças estatísticas significantes entre homens e mulheres (SALLES et al, 2015;SILVA et al, 2018;VIEIRA et al, 2011), o que difere de outros dois estudos investigados, nos quais os homens apresentaram, estatisticamente, maior autoconfiança (MACHADO et al, 2016;PAES et al, 2016 SCHACK, 2017;SALLES et al, 2015;SEELEY et al, 2000;SILVA et al, 2018;VIEIRA et al, 2011).…”
Section: Instrumentounclassified
“…VEALEY; BURTON, 1990). Em síntese, os estudos investigados no presente estudo convergem para mesma direção, ou seja, no geral, os atletas apresentam valores superiores de autoconfiança, quando comparados com os escores de ansiedade somática e cognitiva (FERNANDES et al, 2014;MACHADO et al, 2016;PAES et al, 2016;SALLES et al, 2015).…”
Section: Instrumentounclassified
“…Kurimay, Pope-Rhodius and Kondric (2017) demonstrated a close relationship between coping strategies and anxiety. The findings of Pons, Viladrich, Ramis and Polman (2018) indicated that coping strategies mediated the relationship between competitive anxiety and adaptive behaviors (e.g., commitment to sport). Wadey et al (2014), in turn, affirmed that coping mediated the relationship between competitive anxiety and negative emotions (e.g.…”
Section: Introductionmentioning
confidence: 96%